"It's an Odyssey:" Centering Mexican and Central American Immigrant Entrepreneurs in an Examination of County-Level Sanctuary - Tara Carr-Lemke (Journal of Community Engagement and Scholarship)
Using a comparative case study methodology, this research explores how Mexican and Central American immigrant entrepreneurs in two types of county-level sanctuary contexts (limited and robust) operate their enterprises. Through interviews with 48 small-scale entrepreneurs and 52 organizational contacts facilitated in part through lead local community partners, the study explores entrepreneurs’ perceptions of sanctuary as a factor affecting their business decisions. Self-employment and business registration data from the American Community Survey (ACS) provide context for the narratives. This research suggests that sanctuary policy has an indirect but contributing effect on entrepreneurs’ decision-making and livelihoods. Interviews substantiate the key roles federal and state policy play in shaping the entrepreneurial landscape for immigrants at the county level across sanctuary types. The research illuminates the multi-scalar environment in which immigrant entrepreneurs are embedded and the strategic choices they make with the tools at their disposal. Key recommendations for business ecosystems—including an emphasis on access to driver’s licenses and culturally responsive, multilingual resources—are highlighted. The insights of entrepreneurs deepen understanding of existing theory about immigrant entrepreneurship and the effects of sanctuary policy on immigrant choices.